2013
DOI: 10.1007/s10620-013-2812-9
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and Comorbidity Are Associated with a Lower Early Virologic Response in Hepatitis C Patients Treated with First Generation Protease Inhibitor Triple Therapy: A Preliminary Analysis

Abstract: These preliminary treatment data demonstrate that increased polypharmacy and higher degrees of comorbidity decrease RVR and eRVR rates among patients receiving first generation PI-containing TTx regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The U.S. Center for Medicare and Medicaid Services estimates that polypharmacy costs more than U.S. $50 billion annually. 17 Polypharmacy contributes to health care costs to the patient as well. A retrospective cohort study found that polypharmacy was associated with an increased risk of taking a potentially inappropriate medication, increased clinic visits, and rehospitalization with an approximately 30% increase in medical costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The U.S. Center for Medicare and Medicaid Services estimates that polypharmacy costs more than U.S. $50 billion annually. 17 Polypharmacy contributes to health care costs to the patient as well. A retrospective cohort study found that polypharmacy was associated with an increased risk of taking a potentially inappropriate medication, increased clinic visits, and rehospitalization with an approximately 30% increase in medical costs.…”
mentioning
confidence: 99%
“…Polypharmacy is recognized as an expensive practice. The U.S. Center for Medicare and Medicaid Services estimates that polypharmacy costs more than U.S. $50 billion annually 17 . Polypharmacy contributes to health care costs to the patient as well.…”
mentioning
confidence: 99%
“…The placement of a TIPS is also known to decrease CYP3A activity [22, 26] which may have contributed to the hepatic decompensation of the antiviral therapy in our two patients. Polypharmacy is also known to blunt RVR rates among patients receiving first-generation PIs [27].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be explained by the fact that patients presenting more comorbidities and, subsequently taking more drugs at baseline and presenting more DDIs, were less adherent to treatment. In patients receiving pegIFN and RBV, antiviral regimen complexity has been identified as a predictor of SVR and, in a small cohort of patients treated with first generation NS3/4A PIs, polypharmacy and comorbidity were associated with a lower early virological response .…”
Section: Discussionmentioning
confidence: 99%